2013
DOI: 10.2337/db12-1116
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 21 Mediates Specific Glucagon Actions

Abstract: Glucagon, an essential regulator of glucose homeostasis, also modulates lipid metabolism and promotes weight loss, as reflected by the wasting observed in glucagonoma patients. Recently, coagonist peptides that include glucagon agonism have emerged as promising therapeutic candidates for the treatment of obesity and diabetes. We developed a novel stable and soluble glucagon receptor (GcgR) agonist, which allowed for in vivo dissection of glucagon action. As expected, chronic GcgR agonism in mice resulted in hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
204
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(219 citation statements)
references
References 34 publications
12
204
2
1
Order By: Relevance
“…Omar et al (19) recently provided data supporting a contributing role for GLP-1 in glucose homeostasis of STZ-treated Gcgr 2/2 mice by showing animals administered the GLP-1 receptor (GLP-1R) peptide antagonist, exendin-4 , display poorer glucose tolerance compared with animals that had not received the antagonist. This report also indicated circulating levels of fibroblast growth factor 21 (FGF21) are increased in Gcgr 2/2 mice, a finding paradoxical to other studies showing activation of the GCGR increases hepatic and circulating FGF21 levels (20,21). The combination of exendin-4 and FGF21 antisera worsened the glucose excursion for animals undergoing an oral glucose tolerance test (OGTT) (19 mice and in insulinopenic wild-type and Glp-1r 2/2 animals treated with a high-affinity GCGR antagonist antibody.…”
contrasting
confidence: 51%
“…Omar et al (19) recently provided data supporting a contributing role for GLP-1 in glucose homeostasis of STZ-treated Gcgr 2/2 mice by showing animals administered the GLP-1 receptor (GLP-1R) peptide antagonist, exendin-4 , display poorer glucose tolerance compared with animals that had not received the antagonist. This report also indicated circulating levels of fibroblast growth factor 21 (FGF21) are increased in Gcgr 2/2 mice, a finding paradoxical to other studies showing activation of the GCGR increases hepatic and circulating FGF21 levels (20,21). The combination of exendin-4 and FGF21 antisera worsened the glucose excursion for animals undergoing an oral glucose tolerance test (OGTT) (19 mice and in insulinopenic wild-type and Glp-1r 2/2 animals treated with a high-affinity GCGR antagonist antibody.…”
contrasting
confidence: 51%
“…All these effects were attributed to a glucagon-induced release of FGF21, which has lipolytic activity. Actually, recent reports demonstrate that FGF21 also mediates other different glucagon actions, as we previously commented (147) . Given that the lipolytic action of glucagon is blunted in denervated rats, its effect on adipose tissue has also been associated with sympathetic signals (156) .…”
Section: Other Effects Of Glucagonmentioning
confidence: 99%
“…In the present study, the augmented energy expenditure was attributed to glucagon alone. Similarly, chronic glucagon receptor agonism in dietinduced obese mice lowered food intake, body weight, fat mass and cholesterolaemia while increasing energy expenditure (147) . The actions of glucagon were mediated by FGF21.…”
Section: Therapeutic Potential Of Modulating Glucagon Secretion and Amentioning
confidence: 99%
“…These results demonstrate that hepatic MKP-1 is required for the transcriptional expression of FGF21 in hepatocytes and implies that MAPK activity suppresses FGF21 transcriptional responsiveness. To identify which MAPK suppresses FGF21 expression, hepatocytes from Mkp-1 fl/fl mice were transiently transfected with the FGF21 luciferase reporter and were preincubated with MAPK inhibitors of p38 MAPK (SB203580), JNK (SP60015), and MEK (U0126) prior to stimulation with glucagon to promote both the expression of MKP-1 and FGF21 (32,33). We found that inhibition of p38 MAPK significantly relieved suppression of FGF21 promoter activity (Fig.…”
Section: Generation Of Liver-specific-mkp-1-deficient Micementioning
confidence: 99%